Educational management and organizational climate in public educational institutions of primary education level of Huanta - Ayacucho - Rivas Martínez, Norma (2021)
The research was carried out with the objective of knowing the relationship that exists between educational management and the organizational climate in educational institutions of primary education level in the urban area of the Huanta district. Descriptive research and correlational design. In it, the questionnaire on educational management and organizational climate was used as an instrument, which was applied to a sample of 80 teachers. The statistical treatment was carried out using the Kendall's Taub test because the values presented by the instruments are on an ordinal scale. Likewise, the result obtained allows to conclude that there is a significant relationship between educational management and the organizational climate in educational institutions of primary education level in the urban area of the Huanta district. (tb = 0.701, p = 0.000 <0.05).